Rekindling the flame: erythema Induratum of bazin as a manifestation of latent tuberculosis - Sailaja, Kambhampati; Manasa, Yeluri; Raj Kirit, E. P.; Kiran, Attili Sasi (International Journal of Research in Medical Sciences, 2025)
Erythema Induratum of Bazin is considered a type of tuberculid—a hypersensitivity reaction to Mycobacterium tuberculosis antigens in individuals with underlying tuberculosis infection. EIB primarily occurs in middle-aged women but can also be seen in men, particularly those with predisposing conditions such as diabetes or vascular insufficiency. We report a case of erythema Induratum of Bazin in an elderly diabetic male who present with chronic recurrent, tender erythematous plaques with oozing, crusting and ulceration over both lower limbs with a past history of pleural tuberculosis. Initially he was treated with doxycycline and hydroxychloroquine, but his lesions worsened. However, after starting ATT his condition improved. Early diagnosis and treatment are crucial in preventing associated morbidity and complications.